Build a Responsive Website with a Modern Flat Design - Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2014)
"The days of PHP to HTML5 are dead. No longer do you need to cut up an entire design in Photoshop to use great looking templates for web design. In this course, you will learn how to use a website template to create a responsive website using CSS and HTML5 without endless Photoshop slicing. New CSS functionality allows you to cut your design time in half, and this course shows you how. You will learn by using a real responsive design template with a great looking flat design. You will be walked through every step of using this template, and by the end of the course you will be able to transfer these skills to any template on the market."--Resource description page.
Title from resource description page (viewed December 9, 2014)
Presenter, Stone River eLearning.
Keywords: Web site development; Cascading style sheets; HTML (Document markup language); Electronic books